1995
DOI: 10.1172/jci117791
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutation of human immunoglobulin V genes in the X-linked HyperIgM syndrome.

Abstract: Somatic mutation of Ig variable regions occurs prominently in germinal centers, but it has been debated whether the mutation process initiates in germinal centers or is activated before germinal center entry of B cells. We have analyzed for the presence of somatic mutation in Ig gene rearrangements of the nonpolymorphic human VH6 gene in the X-linked HyperIgM syndrome, which is associated with defective CD40 ligand expression and absence of germinal centers and generation of memory B lymphocytes. IgM and rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 40 publications
(36 reference statements)
1
29
0
Order By: Relevance
“…It should be noted that an alternative way to acquire somatic V H gene mutations has been described in the hyper-IgM syndrome because of a nonfunctional CD40 -CD154 interaction leading to no development of germinal centres (Durandy and Honjo, 2001). However, the mutation frequency in the hyper-IgM syndrome (usually o2%) (Chu et al, 1995;Monson et al, 2001;Weller et al, 2001) is below the cutoff level used to distinguish between mutated and unmutated CLL cases. Hence, it seems unlikely that the mutated CLL cases had acquired V H gene mutations by the alternative CD40-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that an alternative way to acquire somatic V H gene mutations has been described in the hyper-IgM syndrome because of a nonfunctional CD40 -CD154 interaction leading to no development of germinal centres (Durandy and Honjo, 2001). However, the mutation frequency in the hyper-IgM syndrome (usually o2%) (Chu et al, 1995;Monson et al, 2001;Weller et al, 2001) is below the cutoff level used to distinguish between mutated and unmutated CLL cases. Hence, it seems unlikely that the mutated CLL cases had acquired V H gene mutations by the alternative CD40-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…and X-linked lymphoproliferative disorder, who lack functional germinal centers, but do show some SHM. 43,44 Multiple other studies have also shown germinal centerindependent SHM. 45,46 Very recently, Warsame and associates showed evidence of ongoing mutations in microdissected monocytoid B cells.…”
Section: Cell Of Originmentioning
confidence: 90%
“…CD40 knockout mice have impaired immune responses and cannot develop germinal centers (41,42). In humans, the X-linked HIGM syndrome which results from the absence of functional CD40L leads to a defect in germinal center formation, the lack of isotype switch recombination, and the accumulation of IgM with no or very few somatic mutations (46,52). Indeed, in our previous study, the presence of somatic mutations in V H 6 genes from a peculiar HIGM patient was associated with the transient expression of CD40L at the surface of his activated T cells (32).…”
Section: Discussionmentioning
confidence: 99%